lncRNA SNHG1 induced by SP1 regulates bone remodeling and angiogenesis via sponging miR-181c-5p and modulating SFRP1/Wnt signaling pathway - Xiao Yu (BMC, 2021)
Abstract Background We aimed to investigate the functions and underlying mechanism of lncRNA SNHG1 in bone differentiation and angiogenesis in the development of osteoporosis. Methods The differential gene or proteins expressions were measured by qPCR or western blot assays, respectively. The targeted relationships among molecular were confirmed through luciferase reporter, RIP and ChIP assays, respectively. Alkaline phosphatase (ALP), alizarin red S (ARS) and TRAP staining were performed to measure the osteoblast/osteoclast differentiation of BMSCs. The viability, migration and angiogenesis in BM-EPCs were validated by CCK-8, clone formation, transwell and tube formation assays, respectively. Western blot and immunofluorescence detected the cytosolic/nuclear localization of β-catenin. Ovariectomized (OVX) mice were established to confirm the findings in vitro. Results SNHG1 was enhanced and miR-181c-5p was decreased in serum and femoral tissue from OVX mice. SNHG1 directly inhibited miR-181c-5p to activate Wnt3a/β-catenin signaling by upregulating SFRP1. In addition, knockdown of SNHG1 promoted the osteogenic differentiation of BMSCs by increasing miR-181c-5p. In contrast, SNHG1 overexpression advanced the osteoclast differentiation of BMSCs and inhibited the angiogenesis of BM-EPCs, whereas these effects were all reversed by miR-181c-5p overexpression. In vivo experiments indicated that SNHG1 silencing alleviated osteoporosis through stimulating osteoblastogenesis and inhibiting osteoclastogenesis by modulating miR-181c-5p. Importantly, SNHG1 could be induced by SP1 in BMSCs. Conclusions Collectively, SP1-induced SNHG1 modulated SFRP1/Wnt/β-catenin signaling pathway via sponging miR-181c-5p, thereby inhibiting osteoblast differentiation and angiogenesis while promoting osteoclast formation. Further, SNHG1 silence might provide a potential treatment for osteoporosis. Graphic abstract